COMMUNICATIVE STRATEGIES USED BY TEACHERS IN L2 TEACHING - Wahyuningsih Usadiati (ISSN)
Many studies on teacher talk have been done in various parts of the world, and most of them concluded the dominance of teacher in L2 classrooms of young school age learners. This is not surprising since young learners still need supervisions in the use of L2, because they do not have initiative or are not creative enough to use the language. Most of the above studies used their own format of observations due to the unavailability of a standard format. Thus, the result of the study varies in forms. This study supports the study on dominance of the teacher talk to communicate to convey instructions in L2 learning. Various features of communicative strategies occur, but the most preferred ones are code-switching and translation intended to be in the level of comprehensible input of the students.